2001
DOI: 10.2460/ajvr.2001.62.1876
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of porcine reproductive and respiratory syndrome virus in mammary gland secretions of sows

Abstract: Naïve sows inoculated late in gestation shed PRRS virus in mammary secretions. Previous vaccination appeared to prevent shedding during the subsequent lactation. Results for samples obtained from sows in commercial herds suggested that virus shedding in mammary gland secretions of such sows is uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…This differs from previous studies, which report an extensive, although variable and discontinuous, shedding of PRRSV in semen, as detected by swine bioassay and reverse-transcriptase PCR (RT-nPCR) (Swenson and others 1994, Christopher-Hennings and others 1995, 2001. Although both of these techniques are highly sensitive, in this study PRRSV was detected by virus isolation instead of viral nucleic acid determination by RT-nPCR because the main objective was to determine the elimination of infectious virus potentially involved in PRRS transmission by different routes.…”
Section: Referencescontrasting
confidence: 91%
“…This differs from previous studies, which report an extensive, although variable and discontinuous, shedding of PRRSV in semen, as detected by swine bioassay and reverse-transcriptase PCR (RT-nPCR) (Swenson and others 1994, Christopher-Hennings and others 1995, 2001. Although both of these techniques are highly sensitive, in this study PRRSV was detected by virus isolation instead of viral nucleic acid determination by RT-nPCR because the main objective was to determine the elimination of infectious virus potentially involved in PRRS transmission by different routes.…”
Section: Referencescontrasting
confidence: 91%
“…PPRSV can be also shed in urine [47, 50] and mammary gland secretions [43, 49]. In experimentally infected sows, genotype 2 PRRSV was detected by RT-PCR in the first day of lactation [43].…”
Section: Transmission Of Prrsvmentioning
confidence: 99%
“…In experimentally infected sows, genotype 2 PRRSV was detected by RT-PCR in the first day of lactation [43]. Wagstrom et al [49] showed that naïve sows inoculated late in gestation shed PRRSV in colostrum and milk, but only for a limited number of days and in low concentrations, as determined by virus isolation and titration. In addition, vaccination of sows seemed to prevent shedding during subsequent lactations, and the virus was not detected in any of the milk samples collected from 181 sows of 8 endemically infected herds.…”
Section: Transmission Of Prrsvmentioning
confidence: 99%
“…The virus can be found in heart, thymus, spleen, brain, testes and ovaries (Rossow et al, 1994;Halbur et al, 1996a;Rossow et al, 1996;Duan et al, 1997;Sur et al, 1997;Thanawongnuwech et al, 1997;Sur et al, 2001). Virus shedding occurs from many sites including saliva, nasal secretions, urine, semen, feces and mammary secretions and the shedding is believed to be intermittent (Rossow et al, 1994;Wills et al, 1997;Wagstrom et al, 2001). …”
Section: Pathogenesis Of Prrsvmentioning
confidence: 99%
“…Colostrum of those 12 sows was collected within 6 hours after farrowing and assayed for SN antibodies. Colostrum was collected, processed and assayed as previously described (Wagstrom et al, 2001). …”
Section: Experimental Designmentioning
confidence: 99%